2006
DOI: 10.1111/j.0014-3820.2006.tb01854.x
|View full text |Cite
|
Sign up to set email alerts
|

Live Fast, Die Young: Trade-Offs Between Fitness Components and Sexually Antagonistic Selection on Weaponry in Soay Sheep

Abstract: Abstract. Males are predicted to compete for reproductive opportunities, with sexual selection driving the evolution of large body size and weaponry through the advantage they confer for access to females. Few studies have explored potential trade-offs of investment in secondary sexual traits between different components of fitness or tested for sexually antagonistic selection pressures. These factors may provide explanations for observed polymorphisms in both form and quality of secondary sexual traits. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 72 publications
3
96
3
1
Order By: Relevance
“…Extensive evidence for individual variation in the quality of female mammals and birds has been reported (Cobley et al 1998;Festa-Bianchet 1998;Gaillard et al 1998;Pomeroy et al 1999;Crocker et al 2001;Tavecchia et al 2005). Early reproduction has, however, been reported to be costly in several birds (Pyle et al 1997;Barbraud and Weimerskirch 2005), female squirrels (Descamps et al 2006), female reindeer breeding as calves (Reimers et al 2005), and male Soay sheep breeding as lambs (Robinson et al 2006). We also found a marked eVect of experience as the weaning success peaked for multiparous females, being lowest for Wrst-time breeders (Forslund and Pärt 1995;Weladji et al 2006).…”
Section: Discussionmentioning
confidence: 48%
“…Extensive evidence for individual variation in the quality of female mammals and birds has been reported (Cobley et al 1998;Festa-Bianchet 1998;Gaillard et al 1998;Pomeroy et al 1999;Crocker et al 2001;Tavecchia et al 2005). Early reproduction has, however, been reported to be costly in several birds (Pyle et al 1997;Barbraud and Weimerskirch 2005), female squirrels (Descamps et al 2006), female reindeer breeding as calves (Reimers et al 2005), and male Soay sheep breeding as lambs (Robinson et al 2006). We also found a marked eVect of experience as the weaning success peaked for multiparous females, being lowest for Wrst-time breeders (Forslund and Pärt 1995;Weladji et al 2006).…”
Section: Discussionmentioning
confidence: 48%
“…In birds, social monogamy makes separating the contributions of female and male age from reproductive performance traits challenging, although a few studies have found evidence of sex-differences in aging of reproductive performance traits (Lecomte et al, 2010; Reed et al, 2008; Reid et al, 2003), or interactions between male and female age influencing such traits (Auld and Charmantier, 2011). In mammals, age-dependent fecundity trajectories have been compared between sexes in wild red deer and Soay sheep; both studies suggested that age-related declines begin slightly later but progresses more rapidly in males than in females (Nussey et al, 2009; Robinson et al, 2006), although the generality of this pattern remains to be confirmed.…”
Section: Understanding the Causes And Consequences Of Variation Inmentioning
confidence: 99%
“…Horn shape diversity is part of biological richness and seems to have evolutionary importance. Horn shape diversity has been associated with environment-dependent and sex-dependent fitness (Moorcroft et al 1996;Robinson et al 2006). Taking into account the key feature of true domestication cited above, the aim to select for horn shape in Capra pyrenaica is a clear step toward the 'semi-domestication' of the species.…”
Section: The Significant Choice Of Common Namesmentioning
confidence: 99%